CURRICULUM AND THE PROGRESS OF HUMAN CIVILIZATION IN THE WORLD - Setiyono, Junaedi (MAGISTRA, 2012)
Teacher is hoped to be the spearhead of the progress of human civilization. Teacher needs to have a toolwhich enables him or her to perform such a role. The tool which is the most likely to be hoped is curriculum ofwhich he or she works with. The problem is what kinds of curriculum which functions as a reliable and practicaltool. The answer is that such a curriculum must be a standardized one. Then, the teacher must be able totranslate what is intended by the curriculum in the classroom. Furthermore, the teacher must have the abilityto be the curriculum developer.The other problem that needs an attention if we want to discuss the role of teacher dealing with theprogress of human civilization is about the educational reformation. The other consideration is about theconcept of teacher as an investment not only as an employee as the worker of factory. The welfare of teachersis also the object of consideration.Key words: curriculum, human civilization, and teacher